VD_FINDINFO Décision / 2013 / 966 vom 2. September 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, VOLDROIT PÉNAL, VIOLATION DE DOMICILE | 139 CP, 186 CP, 319 CPP (CH), 393 al. 1 let. a CPP (CH)